2010
DOI: 10.1111/j.1949-8594.2009.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

How Preservice Teachers Interpret and Respond to Student Geometric Errors

Abstract: Recognizing and responding to students' thinking is essential in teaching mathematics, especially when students provide incorrect solutions. This study examined, through a teaching scenario task, elementary preservice teachers' interpretations of and responses to a student's work on a task involving reflective symmetry. Findings revealed that a majority of preservice teachers identified the student's errors from conceptual aspects of reflection rather than from procedural aspects. However, when they responded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 48 publications
(56 reference statements)
1
31
0
2
Order By: Relevance
“…This is similar to the findings of the studies by Son & Sinclair (2010), Baki & Kartal (2004). Another important finding of the study indicated that the participants did not use mathematical terminology and jargon in identifying the mistakes of the student.…”
Section: Results Discussion and Suggestionssupporting
confidence: 92%
“…This is similar to the findings of the studies by Son & Sinclair (2010), Baki & Kartal (2004). Another important finding of the study indicated that the participants did not use mathematical terminology and jargon in identifying the mistakes of the student.…”
Section: Results Discussion and Suggestionssupporting
confidence: 92%
“…While some studies reported a strong intersection between teachers' content knowledge (CK) and their ability to evaluate and respond to children's mathematical work (Baumert et al, 2010), others showed that strong CK does not necessarily lead to the development of PSTs' ability to analyze students' strategies (Son & Sinclaire, 2010;Bartell, Webel, Bowen, & Dyson, 2013;Peterson & Leatham, 2010). For example, Bartell et al (2013), in examining the role CK plays in PSTs' ability to recognize children's responses (i.e., specialized content knowledge), reported that CK is not sufficient for supporting PSTs' analyses of children's thinking.…”
Section: Introductionmentioning
confidence: 98%
“…Son and Sinclair (2010) conducted interviews with a group of pre-service teachers (PSTs) to examine how they would evaluate and respond to a student's error on a problem of reflecting a flag across a diagonal line. Over half of the PSTs in the study evaluated the student's work according to the properties of reflection in relation to the perpendicular bisector.…”
Section: Students' Thinking About Reflections and Reflective Symmetrymentioning
confidence: 99%